Over-represented and misunderstood: Pacific young people and juvenile justice in NSW. Issue 4 (December 2017) - Liddell, Marg; Blake, Meredith; Singh, Supriya
In New South Wales, Australia, statistics show that Pacific young people are over-represented in the juvenile justice system. They enter later than other young offenders, frequently for violent offending. Drawing on research with Pacific young people on correctional orders, their families and communities, we outline the reasons for their over-representation using a risk and protective paradigm. Family connections, religious faith and cultural identity are reportedly strong for Pacific young people, but they struggle to negotiate differences between Pacific and Australian cultures. Misunderstanding of these issues and Pacific young people's typical offending trajectory results in a lack of interventions to reduce this offending behaviour. This article makes a contribution to knowledge of a rarely researched group of young people in the juvenile justice system. It highlights the need for increased awareness of issues that Pacific young offenders face.